Different properties between spontaneous and volume‐activated chloride currents in human nasopharyngeal carcinoma and its normal counterpart cells. (1st August 2019) - Tang, Xinwei; Feng, Jiezhu; Peng, Zihan; Hou, Xiuying; Zuo, Wanhong; Chen, Lixin; Wang, Liwei; Zhu, Linyan
Abstract : Although the spontaneous chloride currents (SCC) have been well studied in the normal cells, its properties and roles in neoplasms cells are still unknown. Here, we found that the SCC was manifested in the poorly differentiated human nasopharyngeal carcinoma CNE‐2Z cells, with some differences such as lower occurrence and bigger current density than those of the volume‐activated chloride currents (VACC). NPPB, a chloride channel blocker, inhibited the SCC much stronger than the VACC. Down‐regulation of chloride channel ‐3 (ClC‐3), a volume and mechanically dependent ion channel, could significantly decrease the VACC, but not in SCC. The occurrence, latency, and mean density of the SCC were much lower in the normal nasopharyngeal NP69‐SV40T cells than those in CNE‐2Z cells. Our results demonstrated that the spontaneous electrical reactivity of neoplasm cells is higher than that of normal cells, which probably relates to their high physiological activity of neoplasm cells. Significance of the study: Spontaneous chloride currents (SCC) are well known in excitable tissues and regulate a variety of physiological and pathophysiological processes. During our researching on the volume‐activated chloride currents (VACC) in human nasopharyngeal carcinoma CNE‐2Z cells, SCC could be also observed with different properties from VACC. Meanwhile, the occurrence, latency, and mean density of the SCC were much higher in CNE‐2Z cells than those in normal nasopharyngeal NP69‐SV40T cells. Our results revealed the expression and characteristics of SCC in carcinoma cells and provided a preliminary experimental basis for further exploring the function of SCC in tumour cell biology.